A composite temporary plugging agent material and preparation method thereof
By using composite temporary plugging agent materials, including low-density polyethylene, polylactic acid, N,N-ethylene bisstearamide and wollastonite, the problems of traditional temporary plugging agent materials not tolerate high temperature and poor compressive performance in high-temperature deep carbonate reservoirs are solved, and the temporary plugging effect of high temperature and high pressure resistance is achieved, which is suitable for acidification and fracturing technology.
Patent Information
- Application Number
- CN202310668484.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-06-07
AI Technical Summary
Traditional temporary plugging agent materials are not resistant to high temperatures and have poor compressive performance in high-temperature deep carbonate reservoirs, making them difficult to be suitable for acidification and fracturing technology.
Composite temporary plugging agent materials, including low-density polyethylene and polylactic acid as the main agent, N,N-ethylene bisstearamide as the lubricant, and wollastonite as the filler, are prepared by stirring, mixing, melt extrusion and cooling granulation to prepare a temporary plugging agent material that is resistant to high temperature and high pressure.
The composite temporary plugging agent material is high temperature resistant, high pressure resistant, degradable, and the degradation solution is acidic. It can effectively promote crack opening in high-temperature deep carbonate reservoirs and is suitable for acidification and fracturing technology.
Smart Images

Figure CN116875288B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of temporary plugging agents, and in particular to a composite temporary plugging agent material and a preparation method thereof. Background Art
[0002] Globally, 60% of oil and gas reserves exist in carbonate reservoirs. my country's carbonate reservoirs also have a wide range of oil reservoirs. In the process of oil and gas extraction, acid fracturing technology plays an important role. This technology uses an acid system and temporary plugging materials to plug the cracks that have been opened, build up pressure, and force the fracturing cracks to turn and extend. However, traditional temporary plugging materials have poor high temperature resistance and weak pressure resistance, and are not suitable for acid fracturing of high-temperature deep carbonate reservoirs. Based on this, we need to develop a temporary plugging material suitable for acid fracturing of high-temperature deep carbonate reservoirs. Summary of the invention
[0003] The present application provides a composite temporary plugging agent material and a preparation method thereof, which can be applied to acid fracturing of high-temperature deep carbonate reservoirs.
[0004] This application adopts the following technical solutions:
[0005] The present application provides a composite temporary plugging material, comprising the following components by mass: 90-100 parts of a main agent, 2-5 parts of a lubricant, and 5-8 parts of a filler. The main agent comprises low-density polyethylene and polylactic acid, the mass proportion of low-density polyethylene in the main agent is 50-90%, and the mass proportion of polylactic acid in the main agent is 0-40%, and is not 0.
[0006] Furthermore, the particle diameter of low-density polyethylene is 3 mm and the density is 0.95 g / cm 3 , the melt flow rate is 3.1g / min.
[0007] Furthermore, the polylactic acid includes polyracemic lactic acid, and the density of polyracemic lactic acid is 1.2 g / cm 3 , melt flow rate 4.5g / min.
[0008] Further, the lubricant includes N,N-ethylenebisstearamide.
[0009] Further, the filler includes wollastonite.
[0010] The present application provides a method for preparing the composite temporary plugging agent material, comprising the following steps: stirring and mixing the components to obtain a mixture; melt-extruding the mixture and cooling and granulating it to obtain temporary plugging particles; grinding the temporary plugging particles into a preset particle size to obtain a composite temporary plugging agent material.
[0011] Furthermore, before the components are stirred and mixed, the main agent in the components is dried.
[0012] Furthermore, during the drying process, the drying temperature is 60-80° C. and the drying time is 24-30 hours.
[0013] Furthermore, during the stirring and mixing process, the stirring time is 5-10 minutes and the stirring speed is 400-600 r / min.
[0014] Furthermore, during the melt extrusion process, the melt extrusion temperature is 150-180° C., and the melt extrusion time is 20-40 s.
[0015] Compared with the prior art, this application has the following beneficial effects:
[0016] The composite temporary plugging agent material of the present application is resistant to high temperature, high pressure, and degradable, and the degradation fluid is acidic, and can be applied to acid fracturing of high-temperature deep carbonate reservoirs to promote the opening of cracks. In addition, the preparation method of the composite temporary plugging agent material of the present application is simple and easy to promote and produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a graph showing the change in mass of the composite temporary plugging agent material in a 120°C aqueous solution over time;
[0018] Figure 2 This is a curve diagram of the compressive performance of the composite temporary plugging agent material at room temperature in this application. DETAILED DESCRIPTION
[0019] The technical methods in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0020] The present application provides a composite temporary plugging agent material, comprising the following components in parts by mass: 90-100 parts of a main agent, 2-5 parts of a lubricant, and 5-8 parts of a filler.
[0021] The mass fraction of the main agent can be 90 parts, 95 parts, 100 parts, etc. The main agent includes low-density polyethylene (PE-LD) and polylactic acid (PLA), the mass fraction of low-density polyethylene in the main agent is 50-90%, and the mass fraction of polylactic acid in the main agent is 0-40%, and is not 0. The main agent is a composite material prepared by blending low-density polyethylene and polylactic acid.
[0022] The mass proportion of low-density polyethylene in the main agent can be 50%, 60%, 70%, 80%, 90%, etc. Low-density polyethylene is a typical soft and tough polymer with stable physical and chemical properties and good biocompatibility. The particle diameter of the low-density polyethylene selected in this application is 3mm and the density is 0.95g / cm 3 , the melt flow rate is 3.1g / min.
[0023] The mass proportion of polylactic acid in the main agent can be 1%, 10%, 20%, 30%, 40%, etc. Polylactic acid (PLA) is a polymer material with high strength but poor flexibility and excellent biocompatibility. The polylactic acid selected in this application includes poly racemic lactic acid (also known as amorphous poly D, L-lactic acid), and the density of poly racemic lactic acid is 1.2g / cm 3 , melt flow rate 4.5g / min.
[0024] The lubricant is an auxiliary agent. The mass fraction of the lubricant can be 2 parts, 3 parts, 5 parts, etc. The lubricant selected in this application includes N,N-ethylene bisstearamide (EBS). N,N-ethylene bisstearamide, white or milky white powder or granules. Relative density 0.98, molecular weight 593, melting point 142°C, insoluble in water, soluble in hot chlorinated hydrocarbons and aromatic solvents. Widely used in slip agents, anti-adhesion agents, lubricants and antistatic agents. Non-toxic, suitable for internal and external lubricants of PE, PP, PS, ABS resins and thermosetting plastics.
[0025] The filler is an auxiliary agent. The mass fraction of the filler can be 5 parts, 7 parts, 8 parts, etc. The filler selected in this application includes wollastonite. Wollastonite, the main component of which is calcium silicate (CaSiO3), is a white crystal with a β-type crystal form, a mixture of particles in various shapes such as needles, rods and granules, and is used for reinforcement and cost-reducing filling of plastics such as PE and PA.
[0026] The present application provides a method for preparing the composite temporary plugging agent material, comprising the following steps 1 to 4:
[0027] Step 1: Material preparation
[0028] The low-density polyethylene and polylactic acid in the components are dried, and the dried low-density polyethylene and polylactic acid are weighed according to preset mass fractions, and the lubricant and filler of preset mass fractions are weighed.
[0029] During the drying process, the drying temperature is 60-80°C, such as 60, 70, 80°C, and the drying time is 24-30h, such as 24, 26, 28, 30h.
[0030] Step 2: Mixing materials
[0031] The weighed low-density polyethylene and polylactic acid are poured into a mixer and stirred and mixed, and the weighed lubricant and filler are continuously added and stirred and mixed until the mixture is uniformly blended to obtain a mixture.
[0032] During the stirring and mixing process, the stirring time is 5-10 minutes, such as 5, 8, 10 minutes, and the stirring speed is 400-600 r / min, such as 400, 450, 500, 550, 600 r / min.
[0033] Step 3: Melt granulation
[0034] The mixture is melted and plasticized, and the melted and plasticized mixture is extruded to form extruded strips, and the extruded strips are cooled and then chopped to obtain temporary plugging particles.
[0035] During the melt extrusion process, the melt extrusion temperature is 150-180° C., such as 150, 160, 170, 180° C., and the melt extrusion time is 20-40 s, such as 20, 30, 40 s.
[0036] Step 4: Prepare finished product
[0037] The temporary plugging particles are ground into a preset particle size to obtain a composite temporary plugging agent material.
[0038] The following is a detailed description with reference to specific embodiments:
[0039] Example 1
[0040] Formula (the amount of each component is calculated by mass):
[0041] 72 parts of low-density polyethylene, 18 parts of polylactic acid, 3 parts of lubricant, and 7 parts of filler.
[0042] Preparation method:
[0043] Step 1: Material preparation
[0044] Weigh a certain amount of PE-LD and PLA by weight and put them into a forced air drying oven at 80°C for 24 hours. Weigh 72 parts of PE-LD and 18 parts of PLA after drying for 24 hours, respectively, and weigh 3 parts of lubricant and 7 parts of filler.
[0045] Step 2: Mix the materials
[0046] Pour the weighed PE-LD and PLA in a small blender, blend the two raw materials evenly under high-speed stirring (stirring speed is 600r / min), then add the weighed filler and lubricant in step 1 to the resulting mixture, stir at high speed (stirring speed is 600r / min) for 5 minutes to make PE-
[0047] LD, PLA, filler and lubricant are mixed evenly, and the mixture is poured into a mixing bag for standby use.
[0048] Step 3: Melt granulation
[0049] The mixture obtained in step 2 is put into a small twin-screw extruder for melt plasticization, and the melt plasticized mixture is extruded to form an extruded strip, the melt extrusion temperature is 160°C, and the melt extrusion time is 40s. The extruded strip is cooled by an air-cooled conveyor, and the strip sample is pulled into the trough of a pelletizer, and the pelletizer is used to pelletize into temporary plugging particles of 3mm to 4mm.
[0050] Step 4: Prepare finished product
[0051] Use a cryogenic pulverizer to grind the 3mm-4mm temporary plugging particles in step 3 into finished composite temporary plugging agent materials of 20-40 mesh, 40-70 mesh, 70-100 mesh, and 100-200 mesh.
[0052] Example 2
[0053] Formula (the amount of each component is calculated by mass):
[0054] 50 parts of low-density polyethylene, 40 parts of polylactic acid, 2 parts of lubricant, and 5 parts of filler.
[0055] Preparation method:
[0056] Step 1: Material preparation
[0057] Weigh a certain amount of PE-LD and PLA by weight and put them into a 60℃ forced air drying oven for 30 hours. Weigh 50 parts of PE-LD and 40 parts of PLA after drying for 30 hours, and weigh 2 parts of lubricant and 5 parts of filler.
[0058] Step 2: Mix the materials
[0059] Pour the weighed PE-LD and PLA in a small blender, blend the two raw materials evenly under high-speed stirring (stirring speed is 500r / min), then add the weighed filler and lubricant in step 1 to the resulting mixture, stir at high speed (stirring speed is 500r / min) for 8 minutes to make PE-
[0060] LD, PLA, filler and lubricant are mixed evenly, and the mixture is poured into a mixing bag for standby use.
[0061] Step 3: Melt granulation
[0062] The mixture obtained in step 2 is put into a small twin-screw extruder for melt plasticization, and the melt plasticized mixture is extruded to form an extruded strip, the melt extrusion temperature is 180°C, and the melt extrusion time is 20s. The extruded strip is cooled by an air-cooled conveyor, and the strip sample is pulled into the trough of a pelletizer, and the pelletizer is used to cut into temporary plugging particles of 3mm to 4mm.
[0063] Step 4: Prepare finished product
[0064] Use a cryogenic pulverizer to grind the 3mm-4mm temporary plugging particles in step 3 into finished composite temporary plugging agent materials of 20-40 mesh, 40-70 mesh, 70-100 mesh, and 100-200 mesh.
[0065] Example 3
[0066] Formula (the amount of each component is calculated by mass):
[0067] 89 parts of low-density polyethylene, 1 part of polylactic acid, 5 parts of lubricant, and 8 parts of filler.
[0068] Preparation method:
[0069] Step 1: Material preparation
[0070] Weigh a certain amount of PE-LD and PLA by weight and put them into a 70°C forced air drying oven for 28 hours. Weigh 89 parts of PE-LD and 1 part of PLA after drying for 28 hours, and weigh 5 parts of lubricant and 8 parts of filler.
[0071] Step 2: Mix the materials
[0072] Pour the weighed PE-LD and PLA in a small blender, blend the two raw materials evenly under high-speed stirring (stirring speed is 400r / min), then add the weighed filler and lubricant in step 1 to the resulting mixture, stir at high speed (stirring speed is 400r / min) for 10 minutes to make PE-
[0073] LD, PLA, filler and lubricant are mixed evenly, and the mixture is poured into a mixing bag for standby use.
[0074] Step 3: Melt granulation
[0075] The mixture obtained in step 2 is put into a small twin-screw extruder for melt plasticization, and the melt plasticized mixture is extruded to form an extruded strip, the melt extrusion temperature is 150° C., and the melt extrusion time is 30 seconds. The extruded strip is cooled by an air-cooled conveyor, and the strip sample is pulled into a pelletizer slot, and pelletized into temporary plugging particles of 3 mm to 4 mm using the pelletizer.
[0076] Step 4: Prepare finished product
[0077] Use a cryogenic pulverizer to grind the 3mm-4mm temporary plugging particles in step 3 into finished composite temporary plugging agent materials of 20-40 mesh, 40-70 mesh, 70-100 mesh, and 100-200 mesh.
[0078] Test Example 1
[0079] The prepared composite temporary plugging agent material product is tested for solubility and compressive strength. Taking the composite temporary plugging agent material product prepared in Example 1 as an example, the specific testing method is as follows:
[0080] Dissolution time test method: prepare 200 ml of simulated formation water solution in a beaker, add 10 g of the prepared composite temporary plugging agent material product and stir to make it evenly dispersed, then pour it into a high-temperature reactor and seal it. Place the high-temperature reactor in a constant temperature roller furnace heated to a certain temperature and heat it, and record the time it takes for the composite temporary plugging agent material product to be completely dissolved.
[0081] Dissolution rate determination method: prepare 200 ml of simulated formation aqueous solution in a beaker, add 10 g of the prepared composite temporary plugging agent material and stir to make it evenly dispersed, then pour it into a high-temperature reactor and seal it. Place the high-temperature reactor in a constant temperature roller furnace heated to a certain temperature and heat it, and detect the dissolution rate at different times.
[0082] Wherein, dissolution rate = (weight before dissolution - weight after dissolution) / mass before dissolution × 100% (the samples before weighing were dried in a blast oven for 24 hours)
[0083] Method for measuring compressive performance: The prepared composite temporary plugging agent material is made into a 1cm×1cm cylinder by a precision micro injection molding machine, dried in a blast drying oven for 6 hours, and then placed on a universal material testing machine platform for measurement.
[0084] The performance evaluation of the prepared composite temporary plugging agent material finished product is as follows:
[0085] The quality change of the finished composite temporary plugging agent material obtained in Example 1 in a 120°C aqueous solution over time is shown in Figure 1 As shown, it can be seen that the degradation rate of the finished composite temporary plugging agent material obtained in Example 1 is less than 20% at 120°C within 16 hours, indicating that the dissolution rate in the early stage is low, and its temporary plugging properties can be fully exerted in this time period: when 48 hours, the mass loss rate of the finished composite temporary plugging agent material under high temperature conditions of 120°C has reached more than 80%, indicating that the material can be well degraded and loses its plugging effect.
[0086] The compression performance curve of the finished composite temporary plugging agent material prepared in Example 1 at room temperature is shown in Figure 2 As shown, it can be seen that the compressive strength of the finished composite temporary plugging agent material prepared in Example 1 reaches 120 MPa, which is much higher than the compressive strength of temporary plugging agent materials on the market.
[0087] In summary, the composite temporary plugging agent material of the present application is resistant to high temperature, high pressure, and degradable, and the degradation liquid is acidic, and can be applied to the acid fracturing of high-temperature deep carbonate reservoirs to promote the opening of cracks. In addition, the preparation method of the composite temporary plugging agent material of the present application is simple and easy to promote production.
[0088] The above shows and describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present application. Without departing from the spirit and scope of the present application, the present application may have various changes and improvements, and the scope of protection required by the present application is defined by the attached claims, description and their equivalents.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A composite temporary plugging agent material, characterized in that: The composition includes the following components in parts by weight: 90-100 parts of main agent, 2-5 parts of lubricant, 5-8 parts of filler; Wherein, the main agent includes low-density polyethylene and polylactic acid, the mass proportion of the low-density polyethylene in the main agent is 50-90%, and the mass proportion of the polylactic acid in the main agent is 0-40%, and is not 0; The particle diameter of the low-density polyethylene is 3 mm and the density is 0.95 g / cm 3 , melt flow rate is 3.1g / min; The polylactic acid comprises polyracemic lactic acid, and the density of the polyracemic lactic acid is 1.2 g / cm 3 , melt flow rate 4.5g / min.
2. A composite temporary plugging agent material according to claim 1, characterized in that: The lubricant includes N,N-ethylenebisstearamide.
3. A composite temporary plugging agent material according to claim 1, characterized in that: The filler includes wollastonite.
4. A method for preparing the composite temporary plugging agent material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Stirring and mixing the components to obtain a mixture; The mixture is melt-extruded and cooled to granulate to obtain temporary plugging granules; The temporary plugging particles are ground into a preset particle size to obtain a composite temporary plugging agent material.
5. The preparation method according to claim 4, characterized in that: Before stirring and mixing the components, the main agent in the components is dried.
6. The preparation method according to claim 5, characterized in that: During the drying process, the drying temperature is 60-80°C and the drying time is 24-30h.
7. The preparation method according to claim 4, characterized in that: During the stirring and mixing process, the stirring time is 5-10 minutes and the stirring speed is 400-600r / min.
8. The preparation method according to claim 4, characterized in that: During the melt extrusion process, the melt extrusion temperature is 150-180° C., and the melt extrusion time is 20-40 s.
Citation Information
Patent Citations
Expandable biopolymer temporary plug profile control agent and preparation method thereof
CN105647496A
Degradable temporary plugging material and preparation method thereof
CN115287053A